Spotlight on Polyelectrolyte Complexes and Their Medical Application in Drug Delivery - Mina Emaad Taha; Nidhal Khazaal Maraie; Ram Kumar Sahu (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
Polyelectrolyte complexes (PECs) are class of macromolecule compound formed by electrostatic interaction of oppositely charged polymers. The main objective of this review is to show the formation mechanism of PECs and their characterization, factors affecting their formation,